Rural HIV Negative Young Women have Higher Incidence of Early Onset Cancer of the Cervix Compared to their Urban Counterparts in Western Kenya – A Case Study of Jaramogi Oginga Odinga Teaching and Referral Hospital - George Ogutu; Arthur Ajwang; Khama Rogo; Shem Otoi; Benson Estambale (Journal of Medical Care Research and Review, 2025)
Background: Cervical cancer is the second leading cause of cancer incidence and the leading cause of cancer mortality in women in Kenya. At the Jaramogi Hospital (JOOTRH) Kenya we recorded an increase in incidences of early onset cancer of the cervix, mostly in young rural women, who were HIV negative. This informed the need for a study to identify the demographics especially the residences, rural or urban, of the patients. Objective: This study aimed at identifying the residences of the HIV negative women coming with increased incidences of early onset cancer of the cervix. Methodology: A review of hospital records of all patients aged 13-35 years presenting with Cancer of the Cervix regardless of HIV status at time of diagnosis from 2012 - 2019 was done in the retrospective arm of the study and purposive active recruitment of <35 done for the prospective arm from 2020 - 2021. The residences were recorded as either urban or rural as per the demographic data. Findings: HIV+ or HIV- woman in rural area has higher chances of being infected with cervical cancer compared to their counterparts in urban areas, with an odds ratio of 1.3 > 0.004 and 0.76 > 0.004. Conclusion: We concluded that HIV negative rural women are bearing the burden of increasing incidences of Early Onset Cancer of the Cervix at the Jaramogi Oginga Odinga Teaching and Referral Hospital in Western Kenya.